Smart Biomedical and Physiological Sensor Technology X 2013
DOI: 10.1117/12.2015936
|View full text |Cite
|
Sign up to set email alerts
|

Biodiscovery of aluminum binding peptides

Abstract: A reprint from the Proc. of SPIE Vol. 8719, 871909. Approved for public release; distribution unlimited.ii REPORT DOCUMENTATION PAGE Form Approved OMB No. 0704-0188Public reporting burden for this collection of information is estimated to average 1 hour per response, including the time for reviewing instructions, searching existing data sources, gathering and maintaining the data needed, and completing and reviewing the collection information. Send comments regarding this burden estimate or any other aspect of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…[27][28][29][30] We have previously utilized this library to discover peptide binders for several protein targets, such as Anthrax toxin component protective antigen 30,31 and the Staphylococcal enterotoxin B, 32 as well as peptide binders for bulk aluminum. 10,33 We found that E. coli displaying peptide DBAD1 bound well to the surface of bulk aluminum, which is expected to possess a natural oxide (alumina layer). Moreover, through a combination of sequence analysis, modeling and simulation, we showed evidence that the DBAD1 peptide possesses a high helical propensity due to the presence of alanine residues which facilitate the presentation of hydroxyl-containing residues for interaction with the bulk aluminum surface.…”
Section: Introductionmentioning
confidence: 91%
“…[27][28][29][30] We have previously utilized this library to discover peptide binders for several protein targets, such as Anthrax toxin component protective antigen 30,31 and the Staphylococcal enterotoxin B, 32 as well as peptide binders for bulk aluminum. 10,33 We found that E. coli displaying peptide DBAD1 bound well to the surface of bulk aluminum, which is expected to possess a natural oxide (alumina layer). Moreover, through a combination of sequence analysis, modeling and simulation, we showed evidence that the DBAD1 peptide possesses a high helical propensity due to the presence of alanine residues which facilitate the presentation of hydroxyl-containing residues for interaction with the bulk aluminum surface.…”
Section: Introductionmentioning
confidence: 91%